AUDIT TEKNOLOGI INFORMASI APLIKASI SISTEM PERSURATAN TERPADU (SIRANDU) DENGAN METODE TAM DAN WEBQUAL - Ariyani, Dewi Ayu; Ningsih, Dewi Handayani Untari; Santoso, Dwi Budi; Zuliarso, Eri (INTECOMS: Journal of Information Technology and Computer Science, 2024)
In the rapidly evolving landscape of information technology, IT audits play a crucial role in ensuring that applications such as SIRANDU (Integrated Mailing System) adhere to quality standards and meet user acceptance criteria. This research investigates the determinants influencing users' overall evaluations of a website by employing a combined methodology of the Technology Acceptance Model (TAM) and Webqual. Data were gathered through online questionnaires administered via Google Forms to 100 users of the SIRANDU application. Structural Equation Modeling (SEM) analysis reveals significant positive impacts of usability, perceived usefulness, and attitude toward use on user intentions and actual system usage. Nevertheless, the overall assessment of the website remains inadequate. Recommendations include enhancing usability, improving information quality, and refining service interactions to augment user experience and satisfaction. Continuous evaluation and iterative enhancements are advocated to foster greater user satisfaction and broader adoption of the website. Keywords: SIRANDU application, TAM, Webqual, SEM